THE PROBLEMS FACED BY THE TEACHERS IN DEVELOPING SYLLABUS BASED ON SCHOOL-BASED CURRICULUM DEVELOPMENT (KTSP) IN JUNIOR HIGH SCHOOL IN BANDUNG: A DESCRIPTIVE STUDY ON ENGLISH TEACHERS IN BANDUNG - Fitrian Wulandari, - (2008)
Since the new policy has been legalized, the education curriculum in Indonesia has changed and been called as School-Based Curriculum Development. This curriculum necessitates school to develop their own curriculum and syllabus based on the standards given by the educational board. This research tries to find out how the teachers, as a central role in teaching and learning process in school, conduct the syllabus based on the new policy and also problems faced related to it. The method used in this research is a descriptive method. The first step of the study is gathering information by giving the questionnaire to the respondents. After that, interview is conducted to get more information from respondents. Then the study of documentations is also carried out to complete the data. After getting the data, those are analyzed and interpreted. Based on the analysis, some important points as the result of the study in which teachers adapt the syllabus they made from the Syllabus Guidelines. However, problems came not only from internal but also external factor of the teachers and related parties, culture of the teachers and lack of information that teachers have in developing and conducting the syllabus